Low-temperature steam reforming of methanol to produce hydrogen over various metal-doped molybdenum carbide catalysts - Ma, Yufei; Guan, Guoqing; Shi, Chuan; Zhu, Aimin; Hao, Xiaogang; Wang, Zhongde; Kusakabe, Katsuki; Abudula, Abuliti (International journal of hydrogen energy, 2014)
Various transition metals (M = Pt, Fe, Co, and Ni) were selected to support on molybdenum carbides by in-situ carburization metal-doped molybdenum oxide (M-MoOx) via temperature-programmed reaction (TPR) with a final temperature of 700 degree C in a reaction gas mixture of 20% CH4/H2. XRD analysis results indicated that I2-Mo2C phase was formed in the case of Fe, Co, or Ni doping while I--Mo2C phase was appeared with the I2-MoC1ax phase in the case of Pt doping. With the increase in Pt doping amount, more I--MoC1ax phase was produced. As-prepared metal doped molybdenum carbides were investigated as alternative catalysts for the steam reforming of methanol. Comparing with the undoped molybdenum carbide such as I2-Mo2C, metal-doped one showed higher methanol conversion and hydrogen yield. It is found that Pt doped molybdenum carbide had the highest catalytic activity and selectivity among the prepared catalysts and methanol conversion reached 100% even at a temperature as low as 200 degree C, and remained a long-time stability with a stable methanol conversion.